A Clinical Comparison of Intravenous and Epidural Local Anesthetic for Major Abdominal Surgery. Issue 1 (January 2016) - Terkawi, Abdullah S.; Tsang, Siny; Kazemi, Ali; Morton, Steve; Luo, Roy; Sanders, Daniel T.; Regali, Lindsay A.; Columbano, Heather; Kurtzeborn, Nicole Y.; Durieux, Marcel E.
Abstract : Background: Epidural analgesia provides good pain control after many postoperative procedures, but it can lead to complications, has some contraindications, and occasionally fails. Intravenous lidocaine infusion has been suggested as an alternative. We assessed, in our clinical practice, the effects of perioperative intravenous lidocaine infusion compared with epidural analgesia for major abdominal surgery. Methods: We conducted a retrospective review of patients who had received intravenous lidocaine (1 mg/kg per hour) perioperatively after a major abdominal surgery. We matched them with patients who had received epidural analgesia. We tested a joint hypothesis of noninferiority of lidocaine infusion to epidural analgesia in postoperative pain scores and opioid consumption. We assigned a noninferiority margin of 1 point (on an 11-point numerical rating scale) difference in pain and a ratio [mean (lidocaine) / mean (epidural)] of 1.2 in opioid consumption, respectively. Results: Two hundred sixteen patients (108 in each group) were analyzed. Intravenous lidocaine was not inferior to epidural analgesia with respect to pain scores. Lidocaine infusion was inferior to epidural analgesia with respect to opioid consumption. Patients in the lidocaine group had fewer episodes of hypotension and less postoperative nausea and vomiting, pruritus, and urinary retention. Patients receiving lidocaine also had earlier urinary catheter removal and earlier first gastrointestinal function. Daily mental status assessment was similar between the 2 groups. Conclusions: Patients who received systemic lidocaine infusions with the addition of PRN (as needed) opioids administered for breakthrough pain did not have clinically significant differences in pain scores on postoperative day 2 and beyond. Intravenous lidocaine infusion in major abdominal surgery was inferior to epidural analgesia with respect to opioid consumption. However, lidocaine was associated with improvements in several important aspects of recovery.